HUBUNGAN ANTARA KOORDINASI MATA TANGAN DAN KELENTUKAN PERGELANGAN TANGAN DENGAN HASIL KEMAMPUAN SERVICE PANJANG DALAM PERMAINAN BULUTANGKIS SISWA KELAS X SMAN 1 PEMENANG - Nulhadi, Agus; Ashari, L. Hasan; Abdullah , Afritama (LPPM Institut Pendidikan Nusantara Global, 2022)
The problem this research was the lack or still weak ability of long serve in badminton games for class X SMAN 1 Pemenang. The formulation of the problem in this research was whether there is a relationship between eye-hand coordination and wrist flexibility with the results of long serve ability in badminton games for class X SMA 1 Pemenang students. This research aims to determine the relationship between hand eye coordination and wrist flexibility with the results of long serve ability in badminton games for class X SMAN 1 Pemenang. The population in this study were 20 class X students of SMAN 1 Pemenang. Data collection techniques using action tests and documentation. The data analysis technique used multiple linear correlation statistics. From the results of the multiple correlation analysis (R), the value of R x_(1) x_(2) Y = 0.770 is greater than the value of r table with a significant level of 5%, namely 0.444. So it can be concluded that there is a significant relationship between hand eye coordination and wrist flexibility with the results of long serve ability in badminton games for class X SMAN 1 Pemenang.